Biotechnological production and current feasible applications of neokestose: A review - Nalapat Leangnim; Lalida Shank; Kullapa Chanawanno; Chartchai Khanongnuch; Apinun Kanpiengjai (Carbohydrate Polymer Technologies and Applications)
Neokestose is a trisaccharide that consists of a fructosyl unit linked to the glucose moiety of a sucrose acceptor by β-(2,6) glycosidic linkage. It naturally occurs at low levels in some plants as opposed to 1-kestose and inulin-fructooligosaccharides, which are plentiful in chicory root and Jerusalem artichokes. Production of neokestose is limited due to its availability, while expanded applications require further research development to elucidate its other potential properties. In this review, natural sources of neokestose and biotechnological approaches for neokestose production, including fermentation, microbial synthesis, and enzymatic synthesis, have been summarized and discussed to explore the usefulness and applicability of each production approach. The key enzymes associated with neokestose synthesis are 6G-fructan:fructan fructosyltransferase and 6G-fructofuranosidase. Their different catalytic mechanisms, substrate specificity, and natural sources have also been summarized and discussed in this review. Thus far, there have only been a few reports on the physicochemical and biological properties of neokestose. Preliminary investigations on the biological properties of neokestose, such as its prebiotic and chemopreventive properties, would likely gain considerable attention and lead to the discovery of new beneficial properties of neokestose. These outcomes will likely lead to promising new means of neokestose utilization across various industrial applications.